Dwelling Together on Earth: An Ecological Consideration from Bachelard’s Cosmo-analysis - Huang, Kuan-Min (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
In face of the ecological crisis and the illusion of Anthropocene, and in order to escape from such an urgent threat for the whole planet, it is necessary to reconsider the meaning of “the world in which we live together”. Based on the inspiration from Bachelard, this paper proposes to examine three points: a new concept of subjectivity founded on reversibility, an alternative mode of life as dwelling, and an approach of cosmo-analysis. Rhythmanalysis and topo-analysis help us to state the coexistence of heterogeneous rhythms and the valorization of habitable places. The main purpose is to invert the anthropocentrism that treats the environment as instrument to take a cosmic perspective of living together of multiple species. Keywords: Coexistence, Embodiment, Imagination, Place, Reversibility, Rhythm